Aspects of Health-Improving and Sports-Mass Work Students - Valery Panachev (Journal of Global Pharma Technology, 2018)
Currently sports-mass and health-improving work appears to be one of the most important directions in social students’ self-government as well as effective force of persuasion in necessity of students’ physical training and teachers’ professional activity improvement. New era states new innovative problems before all generations. These problems include improvement of life quality, of human health, active way of life, maintenance of peace in the world. One of the basic problems of future social development of state is the quality life improvement, improvement of people’s health and of demographic situation. Today the problems of population’s health, especially of students’ health are the most pressing ones. Up till now the problem of students’ health strengthening by means of physical culture remains acute. In this article we tried to study the peculiarities of dynamic improvement of students’ physical motion in the last decades. The results of students’ motive behavior received during our study predetermined the real interest to active physical culture and sports training. Special students’ interest was provoked by their own model of self-development during the education at university. The decisive role played the stimulation of students’ self-government in motive activity improvement, healthy life-style, systematic physical culture and sports training. All these facts were connected with greater independence in self-development and preparation to the future professional activity. Keywords: Healthy life-style, Students’ self-government, Health strengthening study, Development of physical culture and sport, Health-improving, Sports-mass work.